Ich heiße Kaspar - Van Doorselaer, Willy,Pressler, Mirjam (Dt. Taschenbuch-Verl., 2009)
Dt. Jugendliteraturpreis, Nominierung.
9783423624114
Keywords: Kinderbuch; Abenteuer; Verbrechen; Geschiedene Eltern; Schule; Junge